Uniform thickness in the process of ore-mixed characteristics of particles passing through experimental research - Niu, Xiangdong; Sun, Huafen; Hou, Kepeng (Frontiers in Earth Science, 2023)
The nature of fine particulate matter is caused by the deterioration of the lean ore loss index and the important influence factors of a mine disaster accident. In this paper, fine moraine particles and coarse-grained ore from the Pulang Copper Mine are studied. The flow of fine particles in mixed particles under the condition of uniform ore drawing was studied by using the laboratory 3D physical model test method. This experiment explored the flow of hybrid particles in the system and characteristics of the particle size of fine particles passing through, and suggested a transit index to quantify the draining effect of fine particles. The experimental results show the following: ①Hybrid particles in the flow system of fine particulate matter under their own gravity use mixed ore particles flow in the process of formation of the pore to implement down through sports. ②The fine particles with the particle sizes of 2.5–1.25 mm, 1.25–0.63 mm, 0.63–0.315 mm, and 0.315–0.16 mm all have the flow-through characteristics, and the smaller the particle size, the more significant the flow-through degree. ③The cumulative ore drawing height of fine particles with different particle sizes increases, while the permeability index of the appropriate discharge decreases. ④The relative motion of coarse and fine particles is the internal control factor that leads to the flow of fine particles. The more significant the relative motion of coarse and finely mixed particles is, the more pores are randomly generated in the particle flow system and the larger the pores are, resulting in the more obvious fine particle flow effect. This study provides some theoretical reference value for revealing the flow-through characteristics of the fine particulate matter in the mixed particle flow system. At the same time, it has practical engineering significance for ore lean loss index control and mine disaster accident prevention and control in caving mining.